Adventure Tourism Motivations: A push and pull factor approach - Giddy, Julia K. (Bulletin of Geography. Socio-economic Series, 2018)
The increased growth and commercialization of adventure tourism led to a number of changes in the profile of the individuals who now engage in adventure activities. As a result, previous understandings of adventure tourism motivations may no longer be valid. This study seeks to investigate the influence of these changes by analyzing the motivations of tourists who have engaged in adventure tourism across a range of commercial adventure activities. This is done through data collected from participants in adventure tourism, throughout South Africa, using a push and pull factor approach to motivations. The results show the increasing influence of the experiences with nature in motivations, particularly in the context of pull factors. The role of risk and thrill in motivations, which has been emphasized in previous literature, is found to be relatively minimal among these respondents. Furthermore, adventure tourism experiences are found to be dynamic, with an increasing number of significant factors influencing decision-making. It also demonstrates notable differences in the motivations of participants, based on the type of activity in which they engage.